Estudo sobre a incorporação de nanopartículas de dióxido de titânio em argamassas fotocatalíticas - Fernandes, Cristiane do Nascimento (2017)
The evolution of building materials from prehistory period to current days demonstrates how important it is to obtain the knowledge of these material properties and applications on different research fields in which they are related to, once we intend to solve some of the current environmental problems and at the same time supply the need for better building components. As a test, TiO2 has been incorporated into building materials seeking for a production of a material that does not require major interventions in terms of maintenance, contributes to improve air quality and increase the life time of buildings as results. Therefore, the present research purpose is to verify the photocatalytic activity of TiO2 in mortars, in order to promote the degradation of Sulfur dioxide (SO2), one of the largest existing air pollutants, taking into consideration accelerated aging conditions for the parts subjected to exposure. However, even with the functionality provided by the degradation, when studying alternative materials researchers should seek not to cause significant damage to the physical properties of the materials tested. Thus, characterization experiments were performed as much on the material used to obtain the mortar (cement, sand and titanium dioxide) as on the test specimens in their fresh (consistency and mass density) and on the hardened state (bulk density, flexural tensile strength, compressive strength, water absorption by capillarity and immersion water absorption). For the photocatalytic verification, the prepared mortars were submitted to the exposure of the SO2 chamber (pollutant gas), for accelerated aging, and then moistened and exposed to ultraviolet radiation in the UV-A band, in order to verify the efficiency of the TiO2 on causing the degradation of the SO2. As a qualitative proof of this degradation, SEM/EDS and Infrared techniques were used before exposure to SO2, after exposure to the pollutant gas and after exposure to radiation. After the results were obtained, the conclusion was that the mortars with higher TiO2 content were the ones with the best physical properties, and it was also possible to verify the efficiency of the added substance for the release of SO2 from contaminated mortars.